Analisis Penentuan Sebaran Konsentrasi Klorofil-A dan Produktivitas Primer di Perairan Teluk Saleh menggunakan Citra Satelit Landsat OLI 8 - Erni Kusumawati; Setyo Budi Susilo; Syamsul Bahri Agus; Arifin Taslim; Yulius Yulius (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Chlorophyll-a is a parameter that can determine the primary productivity in the coastal and ocean. Chlorophyll-a is pigment in phytoplankton that used in photosynthesis. Chlorophyll-a concentration can be detected by ocean color remote sensing by using a mathematical model of satellite image data. The purpose of this research is to modify the algorithm of chlorophyll-a concentration of Landsat OLI 8 Satellite Image data and to show the spatial and temporal distribution of chlorophyll-a concentration. The determination of the algorithm is done using a simple linear regression analysis model between ratio of satellite image band data and value of chlorophyll-a in situ data. The algorithm result is C = 0.416 (green / blue) - 0.183 with R² = 0.785 where C is chlorophyll-a concentration (in mg/m3). Using this algorithm, the spatial distribution of surface concentration of chlorophyll-a can be drawn. Based on analysis of primary productivity that potential of fish resources in the Saleh Bay is 1 327 199.83 ton/years.